An exploratory study of reactive guilt appeals - Lwin, Michael; Phau, Ian (International Management Development Association, 2011)
This study explores the relationships between reactive guilt, attitude towards the brand, inferences of manipulative intent and purchase intentions. Results show no relationship between reactive guilt and purchase intentions. However, attitude towards the brand increased the likelihood of purchase intentions. The research suggests that reactive guilt appeals are inappropriate for the durable consumer goods advertisements. It raises an interesting question why so many advertisers are utilising this type of guilt appeal to target consumers. Managerial implications and future directions radiating from the results are discussed.